2008
DOI: 10.1111/j.1532-849x.2007.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6 Months of Aging in Water on Hardness and Surface Roughness of Two Microhybrid Dental Composites

Abstract: The 6-month period of storage in water presented a significant softening effect on the surfaces of the composites, although no significant deleterious alteration was detected for the subsurface hardness. In addition, the storage period had no significant effect on the surface roughness of the materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 25 publications
3
55
1
10
Order By: Relevance
“…When immersed in artificial saliva, all tested dental composites showed no difference between initial and 30 days period. The results of this study are in agreement with other studies 28) , which reported no statistically significant difference in the surface roughness values of composite resins between initial and 180 days of immersion periods in distilled water. Low pH and alcohol may affect the surface integrity of composite resins.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…When immersed in artificial saliva, all tested dental composites showed no difference between initial and 30 days period. The results of this study are in agreement with other studies 28) , which reported no statistically significant difference in the surface roughness values of composite resins between initial and 180 days of immersion periods in distilled water. Low pH and alcohol may affect the surface integrity of composite resins.…”
Section: Discussionsupporting
confidence: 83%
“…Thus it is more susceptible to surface degradation due the low pH and the high presence of alcohol in whisky. The chemical degradation acts also on resin matrix due to the heterogeneous polymerization process of the methacrylate-based monomers 28) . Moreover, the low pH of a solution causes damage to the mechanical performance of composite resins.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably a result of increased interaction -by virtue of increased contact time-between the immersion solutions and resin materials, leading to greater water uptake and higher erosive impact of the acidic conditions on the materials. As reported by Moraes et al 35) , storage for extended time periods in aqueous media are detrimental to the composite surface. Therefore, progressive degradation over a 6-month storage period altered the microstructures of the restorative materials, such that the inorganic particles were no longer provided with a stable structure, predisposing them to filler dislodgment and elution 35) .…”
Section: Discussionmentioning
confidence: 92%
“…As reported by Moraes et al 35) , storage for extended time periods in aqueous media are detrimental to the composite surface. Therefore, progressive degradation over a 6-month storage period altered the microstructures of the restorative materials, such that the inorganic particles were no longer provided with a stable structure, predisposing them to filler dislodgment and elution 35) . The tested restorative materials contained barium glass, silica, and zirconia/ silica fillers.…”
Section: Discussionmentioning
confidence: 92%
“…Various other studies have also determined alterations of composite restorative materials by measuring changes in microhardness 14,18,19) . Besides measuring changes in the micohardness, other mechanical properties of resin based materials could also be tested, such as: flexural strength 20) , surface roughness 21) and fracture toughness 22) . The results of the present study indicate that the alterations due to NaOCl contact of the build-up composites are a superficial phenomenon.…”
Section: Discussionmentioning
confidence: 99%